Effect of tea polyphenols on the fermentation quality, protein preservation, antioxidant capacity and bacterial community of stylo silage - Huang, Yinchao; Qiu, Chenchen; Wang, Yimin; Zhang, Wei; He, Liwen (Frontiers in Microbiology, 2022)
The present study was aimed to evaluate the improvement potential of tea polyphenols (TPP) on silage characteristics and bacterial community. Stylo ensiled with TPP (0, 0.2% or 0.4%, on a fresh basis) were analyzed for fermentation parameter, protein fraction, antioxidant activity and bacterial community after 7, 14, 30 and 60 days fermentation. The addition of TPP resulted in the decrease (P < 0.05) of pH values (5.09 vs 4.91), dry matter loss (11.77% vs 8.02% DM), butyric acid concentration (1.64% vs 1.02% DM) and ammonia-N proportion (13.69% vs 8.98% CP, on Day 30) of stylo silage as well as the increase (P < 0.01) of lactic acid bacteria population (6.17 vs 7.54 cfu/g FM) and true protein content (6.03% vs 7.44% DM), particularly at the first 30 days of ensiling fermentation. It also enhanced the antioxidant activity (e.g., FRAP) and altered the bacterial community of stylo silage, with Clostridium_sensu_stricto_1 and Lachnoclostridium_5 much decreased but Enterobacter and Clostridium still being the dominant genera. It is suggested that TPP could help improve fermentation quality and nutrient preservation of stylo silage, and delay proteolysis process and antioxidant decay.